Feasibility, Safety, and Efficacy of Posterior Wall Isolation During Atrial Fibrillation Ablation: A Systematic Review and Meta-Analysis. (August 2019) - Thiyagarajah, Anand; Kadhim, Kadhim; Lau, Dennis H.; Emami, Mehrdad; Linz, Dominik; Khokhar, Kashif; Munawar, Dian A.; Mishima, Ricardo; Malik, Varun; O'Shea, Catherine; Mahajan, Rajiv; Sanders, Prashanthan
Abstract : Background: The posterior left atrium is an arrhythmogenic substrate that contributes to the initiation and maintenance of atrial fibrillation (AF); however, the feasibility, safety, and efficacy of posterior wall isolation (PWI) as an AF ablation strategy has not been widely reported. Methods: We undertook a systematic review and meta-analysis of studies performing PWI to assess (1) acute procedural success including the ability to achieve PWI and the number of procedure-related complications, (2) Long-term, clinical success including rates of arrhythmia recurrence and posterior wall reconnection, and (3) The efficacy of PWI compared with pulmonary vein isolation on preventing arrhythmia recurrence. MEDLINE, EMBASE, and Web of Science databases were searched in May 2018 to retrieve relevant studies. Results were pooled using a random effects model. Results: Seventeen studies (13 box isolation, 3 single ring isolation, and 1 debulking ablation) comprising 1643 patients (31.3% paroxysmal AF, left atrial diameter 41±3.1 mm) were included in the final analysis. In studies focusing specifically on PWI, the acute procedural success rate for achieving PWI was 94.1% (95% CI, 87.2%–99.3%). Single-procedure 12-month freedom from atrial arrhythmia was 65.3% (95% CI, 57.7%–73.9%) overall and 61.9% (54.2%–70.8%) for persistent AF. Randomized control trials comparing PWI to pulmonary vein isolation (3 studies, 444 patients) yielded conflicting results and could not confirm an incremental benefit to PWI. Fifteen major complications (0.1%), including 2 atrio-esophageal fistulas, were reported. Conclusions: PWI as an end point of AF ablation can be achieved in a large proportion of cases with good rates of 12-month freedom from atrial arrhythmia. Although the procedure-related complication rate is low, it did not eliminate the risk of atrio-esophageal fistula. Registration: URL:http://www.crd.york.ac.uk/prospero . PROSPERO registration number: CRD42018107212. Abstract : Supplemental Digital Content is available in the text.